Platinum Nanoparticles in Biomedicine: Preparation, Anti-Cancer Activity, and Drug Delivery Vehicles - Abed, Atena; Derakhshan, Maryam; Karimi, Merat; Shirazinia, Matin; Mahjoubin-Tehran, Maryam; Homayonfal, Mina; Hamblin, Michael R; Mirzaei, Seyed Abbas; Soleimanpour, Hamidreza; Dehghani, Sadegh; Dehkordi, Farnaz Farzaneh; Mirzaei, Hamed (Frontiers in Pharmacology, 2022)
Cancer is the main cause of morbidity and mortality worldwide, excluding infectious disease. Because of their lack of specificity in chemotherapy agents are used for cancer treatment, these agents have severe systemic side effects, and gradually lose their therapeutic effects because most cancers become multidrug resistant. Platinum nanoparticles (PtNPs) are relatively new agents that are being tested in cancer therapy. This review covers the various methods for the preparation and physicochemical characterization of PtNPs. PtNPs have been shown to possess some intrinsic anticancer activity, probably due to their antioxidant action, which slows tumor growth. Targeting ligands can be attached to functionalized metal PtNPs to improve their tumor targeting ability. PtNPs-based therapeutic systems can enable the controlled release of drugs, to improve the efficiency and reduce the side effects of cancer therapy. Pt-based materials play a key role in clinical research. Thus, the diagnostic and medical industries are exploring the possibility of using PtNPs as a next-generation anticancer therapeutic agent. Although, biologically prepared nanomaterials exhibit high efficacy with low concentrations, several factors still need to be considered for clinical use of PtNPs such as the source of raw materials, stability, solubility, the method of production, biodistribution, accumulation, controlled release, cell-specific targeting, and toxicological issues to human beings. The development of PtNPs as an anticancer agent is one of the most valuable approaches for cancer treatment. The future of PtNPs in biomedical applications holds great promise, especially in the area of disease diagnosis, early detection, cellular and deep tissue imaging, drug/gene delivery, as well as multifunctional therapeutics.